Specifics of communication skills in medicine - Marković, Jovica (PONS - medicinski časopis, 2015)
Abstract: Communication in medicine is considered a core skill of the doctor on the way to successful diagnosis and treatment, and establishing an adequate relationship with the patient. In a similar way, should take place and the communication process between physician-patient and nurse - patient, and between all actors of the medical team and patients. Good communication skills, patience and sensitivity to the problems of the patient are necessary to create mutual trust. It is important to be in communication with the patient never impose your own views, even when we are deeply convinced that whatever we do, we do it for their own good. Communication in health care requires knowledge, competence and technical skills, including the need for continuing active learning and practicing communication skills of all members of the medical team, both doctors and nurses and other staff who work with patients. Key words: communication, medicine, patient, teamwork, empathy